Intensive measurements of gas, water, and energy exchange between vegetation and troposphere during the MONTES Campaign in a vegetation gradient from short semi-desertic shrublands to tall wet temperate forests in the NW Mediterranean basin (Atmospheric Environment)
Abstract MONTES (“Woodlands”) was a multidisciplinary international field campaign aimed at measuring energy, water and especially gas exchange between vegetation and atmosphere in a gradient from short semi-desertic shrublands to tall wet temperate forests in NE Spain in the North Western Mediterranean Basin (WMB). The measurements were performed at a semidesertic area (Monegros), at a coastal Meditrerranean shrubland area (Garraf), at a typical Mediterranean holm oak forest area (Prades) and at a wet temperate beech forest (Montseny) during spring (April 2010) under optimal plant physiological conditions in driest-warmest sites and during summer (July 2010) with drought and heat stresses in the driest-warmest sites and optimal conditions in the wettest-coolest site. The objective of this campaign was to study the differences in gas, water and energy exchange occurring at different vegetation coverages and biomasses. Particular attention was devoted to quantitatively understand the exchange of biogenic volatile organic compounds (BVOCs) because of their biological and environmental effects in the WMB. A wide range of instruments (GC-MS, PTR-MS, meteorological sensors, O3 monitors,…) and vertical platforms such as masts, tethered balloons and aircraft were used to characterize the gas, water and energy exchange at increasing footprint areas by measuring vertical profiles. In this paper we provide an overview of the MONTES campaign: the objectives, the characterization of the biomass and gas, water and energy exchange in the 4 sites-areas using satellite data, the estimation of isoprene and monoterpene emissions using MEGAN model, the measurements performed and the first results. The isoprene and monoterpene emission rates estimated with MEGAN and emission factors measured at the foliar level for the dominant species ranged from about 0 to 0.2 mg m-2 h-1 in April. The warmer temperature in July resulted in higher model estimates from about 0 to ca 1.6 mg m-2 h-1 for isoprene and ca. 4.5 mg m-2 h-1 for monoterpenes, depending on the site vegetation and footprint area considered. There were clear daily and seasonal patterns with higher emission rates and mixing ratios at midday and summer relative to early morning and early spring. There was a significant trend in CO2 fixation (from 1 to 10 mg C m-2 d-1), transpiration (from x 1 to 5 kg C m-2 d-1), and sensible and latent heat from the warmest-driest to the coolest-wettest site. The results showed the strong land-cover-specific influence on emissions of BVOCs, gas, energy and water exchange, and therefore demonstrate the potential for feed-back to atmospheric chemistry and climate.

Metabolic responses of Quercus ilex seedlings to wounding analysed with nuclear magnetic resonance profiling (Plant Biology, 2013)
Plants defend themselves against herbivory at several levels. One of these is the synthesis of inducible chemical defences. Using NMR metabolomic techniques, we studied the metabolic changes of plant leaves after a wounding treatment simulating herbivore attack in the Mediterranean sclerophyllous tree Quercus ilex. First, an increase in glucose content was observed in wounded plants. There was also an increase in the content of C-rich secondary metabolites such as quinic acid and quercitol, both related to the shikimic acid pathway and linked to defence against biotic stress. There was also a shift in N-storing amino acids, from leucine and isoleucine to asparagine and choline. The observed higher content of asparagine is related to the higher content of choline through serine that was proved to be the precursor of choline. Choline is a general anti-herbivore and pathogen deterrent. The study shows the rapid metabolic response of Q. ilex in defending its leaves, based on a rapid increase in the production of quinic acid, quercitol and choline. The results also confirm the suitability of 1H NMR-based metabolomic profiling studies to detect global metabolome shifts after wounding stress in tree leaves, and therefore its suitability in ecometabolomic studies.

Volatile organic compounds in the western Mediterranean basin: urban and rural winter measurements during the DAURE campaign (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2013)
Atmospheric volatile organic compounds (VOCs) have key environmental and biological roles, but little is known about the daily VOC mixing ratios in Mediterranean urban and natural environments. We measured VOC mixing ratios concurrently at an urban and a rural site during the winter DAURE campaign in the northeastern Iberian Peninsula, by means of PTR-MS at both locations: a PTR-Quad-MS at the urban site and a PTR-ToF-MS at the rural site. All VOC mixing ratios measured were higher at the urban site (e. g. acetaldehyde, isoprene, benzene, and toluene with averages up to 1.68, 0.31, 0.58 and 2.71 ppbv, respectively), with the exception of some short-chain oxygenated VOCs such as acetone (with similar averages of 0.7-1.6 ppbv at both sites). The average diurnal pattern also differed between the sites. Most of the VOCs at the urban location showed their highest mixing ratios in the morning and evening. These peaks coincided with traffic during rush hour, the main origin of most of the VOCs analyzed. Between these two peaks, the sea breeze transported the urban air inland, thus helping to lower the VOC loading at the urban site. At the rural site, most of the measured VOCs were advected by the midday sea breeze, yielding the highest daily VOC mixing ratios (e. g. acetaldehyde, isoprene, benzene, and toluene with averages up to 0.65, 0.07, 0.19, and 0.41 ppbv, respectively). Only biogenic monoterpenes showed a clear local origin at this site. In addition, the concentrations of fine particulate matter observed at both sites, together with the synoptic meteorological conditions and radio-sounding data, allowed the identification of different atmospheric scenarios that had a clear influence on the measured VOC mixing ratios. These results highlight the differences and relationships in VOC mixing ratios between nearby urban and rural areas in Mediterranean regions. Further research in other urban-rural areas is warranted to better understand the urban-rural influence on atmospheric VOC mixing ratios under different atmospheric conditions.
APS